2006
DOI: 10.1021/je0600045
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibrium of Binary Mixtures. 1. Ethanol + 1-Butanol, Ethanol + Octane, 1-Butanol + Octane

Abstract: The activity coefficients of the binary mixtures ethanol + 1-butanol, ethanol + octane, and 1-butanol + octane were determined at temperatures of (308.15, 313.15, and 318.15) K. The determination of the vapor phase composition at equilibrium was carried out using headspace gas chromatography analysis. Multiple headspace extraction was used to calibrate the headspace gas chromatograph. Comparison of the phase diagrams produced using standard Legendre orthogonal polynomial techniques with phase diagrams from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
(17 reference statements)
0
17
0
Order By: Relevance
“…By solving eq. ( 4) for minimum and maximum compressibility, the densities are calculated as (20) Over the critical point Zmax=Zmin thus one only solution is calculated by the PR-EOS.…”
Section: Densitymentioning
confidence: 99%
“…By solving eq. ( 4) for minimum and maximum compressibility, the densities are calculated as (20) Over the critical point Zmax=Zmin thus one only solution is calculated by the PR-EOS.…”
Section: Densitymentioning
confidence: 99%
“…For example, alcohols are commonly used as hydrate inhibitors in gas pipelines, 1 utilized to improve the antiknock properties of gasoline, or used as alternative fuel components. 2 Among different alkanols currently used in the petrochemical industries, methanol has significant importance because of its relatively inexpensive production cost. 3 To design and optimize separation process equipment that involves mixtures of methanol + n-alkanes, accurate knowledge of the phase behavior of these highly complex systems is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, as the hydrocarbon mixtures handled in the petrochemical industries are in fact highly complex mixtures comprising a large number of individual hydrocarbon groups, considering all of the species involved would be a significantly cumbersome task. 2 In this regard, a much more tractable approach would be to study model systems of heavy hydrocarbons + methanol, for instance the system of interest in the current work, methanol + n-heptane. A number of isothermal VLE data have been reported in the literature for the methanol + n-heptane binary system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these properties, ethanol-butanol mixture may be considered as promising oxygenated gasoline In order to design applicable oxygenated (nbutanol/ethanol) -gasoline blend, the knowledge of vapor pressure values for the systems containing ethanol, n-butanol and isooctane is necessary. Several studies have been reported for vapor pressure measurement of the binary systems containing isooctane, ethanol and n-butanol [10][11][12]. There was only one study reporting for vapor pressure of the ternary system containing isooctane, n-butanol and 1-hexene (without ethanol) [13].…”
Section: Introductionmentioning
confidence: 99%